Diagnostic Challenges of Cryptococcus neoformans in an Immunocompetent Individual Masquerading as Chronic Hydrocephalus. (20th July 2016) - Mahajan, Kedar R.; Roberts, Amity L.; Curtis, Mark T.; Fortuna, Danielle; Dharia, Robin; Sheehan, Lori
Abstract : Cryptococcus neoformans can cause disseminated meningoencephalitis and evade immunosurveillance with expression of a major virulence factor, the polysaccharide capsule. Direct diagnostic assays often rely on the presence of the cryptococcal glucuronoxylomannan capsular antigen (CrAg) or visualization of the capsule. Strain specific phenotypic traits and environmental conditions influence differences in expression that can thereby compromise detection and timely diagnosis. Immunocompetent hosts may manifest clinical signs and symptoms indolently, often expanding the differential and delaying appropriate treatment and diagnosis. We describe a 63-year-old man who presented with a progressive four-year history of ambulatory dysfunction, headache, and communicating hydrocephalus. Serial lumbar punctures (LPs) revealed elevated protein (153–300 mg/dL), hypoglycorrhachia (19–47 mg/dL), lymphocytic pleocytosis (89–95% lymphocyte, WBC 67–303 mg/dL, and RBC 34–108 mg/dL), and normal opening pressure (13–16 cm H2 O). Two different cerebrospinal fluid (CSF) CrAg assays were negative. A large volume CSF fungal culture grew unencapsulated C. neoformans . He was initiated on induction therapy with amphotericin B plus flucytosine and consolidation/maintenance therapy with flucytosine, but he died following discharge due to complications. Elevated levels of CSF Th1 cytokines and decreased IL6 may have affected the virulence and detection of the pathogen.